Loners, Colleagues, or Peers? Assessing the Social Organization of Radicalization - Holt, Thomas J. (American journal of criminal justice, 2019)
This study explores the utility of a sociological model of social organization developed by Best and Luckenbill ( 1994 ) to classify the radicalization processes of terrorists (i.e., extremist perpetrators who engaged in ideologically motivated acts of violence) who are usually categorized as loner or lone wolf attackers. There are several organizational frameworks used to define or classify violent acts performed by individuals who may or may not have ties to extremist groups, but these studies largely ignore the role of social relationships in radicalization and the extent to which they inform our knowledge of terror. To address this gap, we apply the Best and Luckenbill model of social organization using a qualitative analysis of three case studies of four lone actor or small cell terrorists. The findings demonstrate lone actors are not always true loners in the context of radicalization, and highlights the ways that the Internet and social ties foster the radicalization processes of terror.